EFESIENSI PEMUPUKAN NITROGEN TERHADAP SIFAT FISIK TANAH SERTA HASIL TANAMAN KANGKUNG DARAT MELALUI APLIKASI PUPUK ORGANIK CAIR KRINYU (Ipomea reptans poir) - Charly Mutiara; Stefan Jaghu Renggi (AGRICA, 2020)
The problems faced are the use of inorganic fertilizers that damage the level of soil organic matter decreases, soil structure is damaged, and environmental pollution. This research utilizes liquid organic fertilizer, kirinyu because it has N elements which are high enough to provide yield of ground water spinach plants and soil physical properties. This study aims to determine the effect of nitrogen fertilizer efficiency on soil physical properties and the effect of nitrogen fertilizer efficiency on land kale yield. The study was arranged based on 2 factors: the outcome variable using a randomized block design (RBD) and the variable saving of Soil Physical Properties. The results of statistical analysis show that the efficiency of nitrogen fertilization on the yield of ground water spinach plants has a very significant influence on yield variables which include fresh weight of land spinach tan-1 (g) and fresh weight of water spinach ha-1 (ton). The efficiency of nitrogen fertilization on the yield of ground water spinach plants has a very significant effect with an average increase in each treatment for fresh water spinach per plant by 27.97% and the fresh weight of water spinach per hekatar by 27.97%. The efficiency of nitrogen fertilization on the physical properties of the soil in kangkung cultivation in Lokoboko village has sandy clay soil texture, has a density value of contents ranging from 1.33 g / cm - 1.37 g / cm and soil porosity 45.46% - 50.22 %. The soil color is dominated by 10 YR 2/1 Black and 10 YR 2/2 Very Dark Brown, having soil temperatures ranging from 25,250C - 26,750C.